Principal strain-induced fiber orientation evolution in the Csf/Mg composites with a large deformation. (November 2015) - Tian, Wenlong; Qi, Lehua; Zhou, Jiming; Xu, Yiren
In this article, the fiber orientation evolution in the Csf /Mg composites with a large deformation is investigated. The principal strain-induced fiber orientation evolution mechanism, which states that the fiber orientation evolution in the Csf /Mg composites with a large deformation is determined by the principal strains, is proposed. The fiber orientation distribution factorsF i ( i = 1, 2 and 3 ) taking the form of the principal strains are proposed to quantitatively characterize the fiber orientation distribution in the Csf /Mg composites. The fiber orientation factorsF i s predicted by the finite element simulation based on the principal strain-induced fiber orientation evolution mechanism are compared against thoseF i m measured from the micrographs of the extrusion experiments of Csf /Mg composites. The results demonstrate that the principal strain-induced fiber orientation evolution mechanism is valid and convenient to predict the fiber orientation evolution in the Csf /Mg composites with a large deformation. In the extruded Csf /Mg composites, the fibers are reoriented toward the direction of the maximum principal strain and deviated from the direction of the minimum principal strain.